Discriminatory Behavior among People Living with Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome against Adherence to Antiretroviral Treatment - Indriastuti, Nur Azizah; Ayuningtyas, Ririn (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Globally, human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) is a serious health issue, as the number of sufferers increases from year to year. As there are many HIV/AIDS cases, antiretroviral treatment (ART) regimens’ success is determined by the high adherence of people living with HIV/AIDS (PLWHA) undergoing a treatment regimen. PLWHA adherence in undergoing ART regimens can be influenced by discriminatory behavior toward them. AIM: This study aims to identify discriminatory behavior in PLWHA toward adherence to ART in Yogyakarta. METHODS: This research used a qualitative method with a phenomenology approach. The collection of data was carried out through interviews and observation. Participants totaling seven people were determined by purposive sampling. The data validity employed source triangulation and checked the data back to the participants. Analysis of data was by comparing among categories, marking, and describing descriptively. RESULTS: The results showed that PLWHA got discriminatory behavior around them during ARV treatment, which came from the attitude of health workers and unpleasant experiences from the environment, but this discriminatory behavior did not affect PLWHA adherence to ARV treatment. CONCLUSION: Discriminatory behavior from health workers and the environment around PLWHA did not affect PLWHA adherence during ARV treatment.